2010
DOI: 10.2174/1874418401004010001
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolic Disease after Lung Transplantation: Special Focus on Sirolimus

Abstract: Background: Venous thromboembolism (VTE) is common after lung transplantation. We aimed to review our experience with VTE in lung transplant recipients, while paying attention to the use of sirolimus, a novel immunosuppressive agent that may have prothrombotic effects. Methods: A retrospective review of lung transplant recipients at the University of Pennsylvania from 2000 to 2006 was performed. Demographic data, acute and chronic rejection and survival were included. Clinically apparent VTE episodes and sirol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…There are discordant data in the transplant literature regarding whether sirolimus is prothrombotic. Our findings are consistent with two recently published studies suggesting an associa-tion between sirolimus use and VTE in lung transplant recipients (29,30). An increased risk of thrombotic events has also been noted with the use of sirolimus in liver transplant recipients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There are discordant data in the transplant literature regarding whether sirolimus is prothrombotic. Our findings are consistent with two recently published studies suggesting an associa-tion between sirolimus use and VTE in lung transplant recipients (29,30). An increased risk of thrombotic events has also been noted with the use of sirolimus in liver transplant recipients.…”
Section: Discussionsupporting
confidence: 93%
“…Sirolimus has associated toxicities . Recent studies have found an increased risk of venous thromboembolism (VTE) in lung transplant recipients receiving sirolimus both in a retrospective review and a prospective, randomized, open‐label study comparing immunosuppressive regimens . In addition, the FDA issued a black box warning in 2002 stating that de novo use of sirolimus in liver transplant recipients may be associated with hepatic artery thrombosis based on preliminary results of two multicenter phase II/III trials .…”
mentioning
confidence: 99%
“…This finding was unexpected and supports the hypothesis from a recently published small, single-center, retro- spective study suggesting an association between SIR use and VTE. 13 SIR, also known as rapamycin, is a potent immunosuppressive drug that is increasingly being used for the prevention and treatment of acute and chronic allograft rejection after solidorgan transplantation. This drug exerts its biologic effects by binding to and inhibiting the mammalian target of rapamycin (mTOR), a critical intracellular regulatory kinase involved in protein translation, cell growth and proliferation, angiogenesis and adaptive processes necessary for cell survival during stress.…”
Section: Discussionmentioning
confidence: 99%
“…9 -12 After observing several unexpected cases of venous thromboembolism (VTE) in lung transplant recipients receiving sirolimus, investigators at the University of Pennsylvania retrospectively reviewed and reported on their single-center experience and found a possible association between SIR use and an increased risk of VTE. 13 Although VTE is not uncommon after lung transplantation, its association with a particular immunosuppressive regimen has not been previously reported. 14 -16 To further investigate the question of whether or not SIR increases the risk of VTE, we analyzed data from a recently completed, large, multicenter, prospective, randomized, open-label study of 181 lung transplant recipients comparing acute rejection, chronic rejection, and survival rates between a cohort of patients who received azathioprine (AZA), tacrolimus (TAC), and prednisone (PRED) (Group 1) for maintenance immunosuppression versus a cohort that received SIR, TAC, and PRED (Group 2).…”
mentioning
confidence: 98%
“… described DVT as a risk factor for patient survival (HR 2.43; 95% CI, 1.29–4.64), and Lingaraju et al . found VTE to be associated with poorer survival 3 months after LT.…”
Section: Discussionmentioning
confidence: 93%